Horn Sounds in Transportation Systems and a Cognitive Perspective on the Instant Mood-Condition Disorder. (2017) - Erkan, İlker
Abstract: This study was performed on sidewalks that there can secure movement of pedestrians. The basic theme of the research is how pedestrians are influenced by the sudden hearings of horns in the walking moments. In this study on different horns chord samples were randomly presented during simultaneous Electroencephalogram (EEG) recordings to a total of 48 healthy participants aged between 25–65 years; the elicited brain responses were examined. EEG recording with visual stimuli is performed on 48 subjects at delta, theta, alpha, beta and gamma frequency bands by using 5 different horn sounds which are selected from the real traffic environments. Especially trucks with a high-end horn sound, show very significant differences in the brainwaves of the pedestrians. Therefore, it is very important for pedestrians to make legal arrangements related to the voice of the high horn, especially in the developed countries.